2015
DOI: 10.4081/jlimnol.2015.1269
|View full text |Cite
|
Sign up to set email alerts
|

The freshwater diaptomid copepod fauna (Crustacea: Copepoda: Diaptomidae) of the Western Ghats of Maharashtra with notes on distribution, species richness and ecology

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The species estimators Chao2, Jackknife1 and Bootstrap showed that almost 70-80% of the aquatic beetle diversity was recorded from the study region, suggesting more sampling in the area may reveal additional species. Earlier studies (Foggo et al, 2003;Padhye and Dumont, 2015;Kulkarni and Pai, 2016) showed that the non-parametric richness estimators provided more accurate and precise species richness estimate for freshwater invertebrates. Thakare and Zade (2011) Altitude is known to be a crucial geographical factor that changes characteristics of aquatic habitats and influences the composition of aquatic insects (Garrido et al, 1994;Touaylia et al, 2011) and other aquatic invertebrates (Williams et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The species estimators Chao2, Jackknife1 and Bootstrap showed that almost 70-80% of the aquatic beetle diversity was recorded from the study region, suggesting more sampling in the area may reveal additional species. Earlier studies (Foggo et al, 2003;Padhye and Dumont, 2015;Kulkarni and Pai, 2016) showed that the non-parametric richness estimators provided more accurate and precise species richness estimate for freshwater invertebrates. Thakare and Zade (2011) Altitude is known to be a crucial geographical factor that changes characteristics of aquatic habitats and influences the composition of aquatic insects (Garrido et al, 1994;Touaylia et al, 2011) and other aquatic invertebrates (Williams et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The region was declared as a biodiversity hotspot based mainly on the knowledge about vertebrates, as most of its invertebrate diversity was not well known (Myers et al, 2000). The freshwater ecosystems of NWG are rich in faunal diversity as suggested by recent studies on the freshwater invertebrates (Kulkarni et al, 2015), including crustaceans (Shinde et al, 2014;Padhye and Dahanukar, 2015;Padhye and Dumont, 2015;Padhye and Victor, 2015;Kulkarni and Pai, 2016), rotifers Vanjare et al, 2017) and sponges (Jakhalekar and Ghate, 2013, and vertebrates such as freshwater fishes (Keskar et al, 2018). On the contrary, Thakare and Zade (2011) is the only available report on species richness of aquatic beetles from Melghat tiger reserve, Maharashtra.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, some species also establish prevalently flightless populations in these rock pools. Rich invertebrate communities have been reported from these habitats (Kulkarni & Pai, 2016; Padhye & Dahanukar, 2015; Padhye & Victor, 2015; Shinde et al, 2014). Hydroperiod seems to drive the variation in community composition of passive dispersers in these habitats, and the metacommunity is shaped mainly by species replacements between assemblages (Kulkarni et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, some species also establish prevalently flightless populations in these rock pools. Rich invertebrate communities have been reported from these habitats (Kulkarni & Pai, 2016;Padhye & Dahanukar, 2015;Padhye & Victor, 2015;Shinde et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, this region is interesting for biogeography because of i) a complex geological history; ii) a wide range of altitudes; and iii) a strong seasonality with a distinct rainfall season (Monsoon) (Mani, 1974;Briggs, 2003). This has allowed the formation of various biomes, ranging from tropical to Alpine forests and deserts (Mani, 1974) resulting in a combination of endemic, Oriental, Palaearctic as well as Gondwanan biota (Gower et al, 2002;Whatley and Bajpai, 2006;Koehler and Glaubrecht, 2007;Kulkarni and Pai, 2016). Their presence has been explained by hypotheses like the 'Indian raft' and 'Out of Asia into India' (Chatterjee and Scotese, 1999;Karanth, 2003), but relevance of such scenarios for passively dispersed zooplankton is uncertain.…”
Section: Introductionmentioning
confidence: 99%